The relationship between family social support and quality of life in diabetic female patients - Ali Mousavi; Zahra Vahedi; Zahra Kiaei; Mehrali Rahimi (Gonabad University of Medical Sciences, 2017)
Life quality of diabetic patients is always affected by psychosocial problems, physical disorders, and life style changes. It seems that the perceived social support could intervene in improving the life quality of these patients. The present study was carried out aiming to examine the relation between family social support and life quality of female patients with diabetes. This was a cross-sectional study. The statistical population included 173 diabetic females who were randomly selected from patients referred to Kermanshah diabetes research center. Data were collected using life quality questionnaire (Short Form-36) as well as perceived social support scale. The data analysis indicated that there is a significant correlation between family support and life quality of patients. Furthermore, concerning the components of life quality, there is a significant correlation between family social support and physical performance, physical limitation, tiredness, emotional health, social performance, pain, and general health of patients. However, no significant relation was found between family support and limitation of patients. Results showed that there is a direct relation between family support and the life quality in females with diabetes. Hence, it can be concluded that giving the family support to the female diabetic patients can increase their quality of life.